Beautiful ruins [compact disc, unabridged] : a novel - Walter, Jess, 1965- (HarperAudio, 2012)
The story begins in 1962. On the sun-drenched Italian coastline, a young innkeeper looks out over the incandescent waters of the Ligurian Sea and spies a tall, thin woman approaching him on a boat. She is an actress, an American starlet, and she is dying. The story begins again today when an elderly Italian man shows up on a movie studios back lot, searching for the mysterious woman he last saw at his hotel decades earlier.